Death duties: Workshop on what family physicians are expected to do when patients die - Myers, Kathryn A. (College of Family Physicians of Canada, 2007)
PROBLEM BEING ADDRESSED: Family physicians are often called upon to pronounce and certify the deaths of patients. Inadequate knowledge of the Coroners Act (in the province of Ontario) and of the correct process of certifying death can make physicians uncomfortable when confronted with these tasks. OBJECTIVE OF PROGRAM: To educate family physicians about how to perform the administrative tasks required of them when patients die. PROGRAM DESCRIPTION: The program included an educational video, a tutorial outlining the process of death certification, and discussion with a regional coroner about key features of the Coroners Act. In small groups, participants worked through cases of patient deaths in which they were asked to determine whether a coroner needed to be involved, to determine the manner of death, and to complete a mock death certificate for each case. CONCLUSION: All participants reported a high level of satisfaction with the workshop and thought the main objective of the program had been achieved. Results of a test given 3 months after the workshop showed substantial improvement in participants’ knowledge of the coroner’s role and of the process of death certification.